Effects of rapid weight loss on balance and reaction time in elite judo athletes - Morales, J.; Ubasart, C.; Solana-Tramunt, M.; Villarrasa-Sapiña, I.; González, L. M.; Fukuda, D.; Franchini, E. (International Journal of Sports Physiology and Performance, 2018)
Balance, reaction time, and strength are key factors affecting judo performance. Although ample research has been done examining potential strength changes caused by weight loss prior to competition, changes in balance and reaction time have been overlooked. Purpose: To examine the effects of rapid and progressive weight loss (RWL and PWL) on balance, reaction time, and strength in a group of elite judo athletes. Methods: A total of 38 female and male judo athletes (age = 20.6 [2.6] y) completed balance, reaction-time, and strength assessments 1 wk prior to an official weigh-in (pretest) and immediately after the weigh-in (posttest). The athletes were divided into 3 groups, 1 control group who maintained regular training and eating habits, 1 experimental group who engaged in PWL (<3% reductions in body mass), and a second experimental group who used RWL techniques (>3% reductions in body mass). Results: The RWL group showed significant decreases (P < .05) in balance performance (ellipse area: 4.83 [0.87] vs 6.31 [1.39] mm2 with eyes closed; mean mediolateral velocity: 2.07 [0.2] vs 2.52 [0.45] mm/s with eyes closed; and mean anteroposterior velocity: 2.25 [0.20] vs 2.51 [0.32] mm/s with eyes open and 2.44 [0.26] vs 3.06 [0.56] mm/s in the PWL and control groups maintained performance in all variables. Conclusion: These findings demonstrate negative effects on perceptual motor-skill performance in judo athletes engaging in RWL strategies prior to competition.